Public Relations and LGBTQ+ Equality Issues: Supporting the Rights and Representation of the LGBTQ+ Community in Media and Society - Zulfikar, Zulfikar; Chatun, Sri; Megan, Goldwag; Jonathan, Bouyea (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
The function of Public Relations is very important in shaping public opinion, especially regarding sensitive issues such as LGBTQ+ equality. Since the representation and rights of the LGBTQ+ community are often still limited and biased in the media and society, it is important to examine further how public Relations can support advocacy for these communities. This study aims to investigate Public Relations strategies and actions that support LGBTQ+ equality and assess how effective they are in increasing the positive image of the LGBTQ+ community in the media and general public. This research focuses on identifying Public Relations actions that assist in accepting and respecting LGBTQ+ rights. The research methods used are quantitative and qualitative. This method was chosen for data collection and analysis involving interviews, media content analysis related to the LGBTQ+ equality campaign, and surveys regarding public perceptions of the campaign. The results of this research show that inclusive and educational communication strategies from Public Relations can increase awareness and support for LGBTQ+ issues. Campaigns that highlight personal stories, collaborations with influencers, and advocacy activities are effective in creating a more inclusive and empathetic dialogue in society. This research concludes that Public Relations plays a crucial role in supporting LGBTQ+ equality through effective and inclusive communication approaches. Strong collaboration between Public Relations practitioners, the media, and the LGBTQ+ community is needed to expand LGBTQ+ representation and rights. Public Relations serves as an important intermediary to promote better understanding and social acceptance of the LGBTQ+ community